Temperature effect on mechanical properties of toughened silicone resins - Wu, Yuhong; McGarry, Frederick J.; Zhu, Bizhong; Keryk, John R.; Katsoulis, Dimitris E. (Polymer engineering and science, 2005)
The temperature dependence of mechanical properties of two families of toughened silicone resins was investigated. The first family was representative of hydrosilylation reaction curable silicone resins, and the second representative of condensation reaction curable ones. The hydrosilylation curable resin was cross‐linked with a variety of cross‐linkers, including 1,4‐bis(dimethylsilyl) benzene, 1,1,3,3,5,5,‐hexamethyltrisiloxane, diphenylsilane, and their mixtures. The condensation reaction curable resin and its toughened versions were cross‐linked by silanol condensation. Properties studied included flexural strength, flexural modulus, and fracture toughness KIc. Temperature effect on these properties of the first family of resins was substantial and varied strongly with the type of cross‐linkers. For this family of resins the flexural strength and modulus decreased with a rising temperature. Fracture toughness KIc showed a peaking behavior with the peak appearing at approximately 62°C below the α transition peak. This was explained by the effect of the plastic zone size, and the effect of the network resistance to plastic deformation. The second family of resins also showed decreases in modulus and strength with a higher testing temperature, but the fracture toughness changed little with temperature. POLYM. ENG. SCI., 45:1522–1531, 2005. © 2005 Society of Plastics Engineers